PEMBELAJARAN INKUIRI TERBIMBING BERBANTUAN SIMULASI KOMPUTER TERHADAP HASIL BELAJAR MATERI KESETIMBANGAN KIMIA - Leny Fitriah (Hydrogen: Jurnal Kependidikan Kimia, 2019)
This research uses factorial design 2 x 2. The sample in this research is thestudents of IKIP Kimia Mataram Chemistry study program that follow theBasic Chemistry 2 course in the even semester of academic year 2013/2014with 2 homogenously distributed classes. The sample was taken by clusterrandom sampling technique. One class consists of 21 students who weretaught inquiry led by using computer simulation and other class consists of 22students with guided Inquiry. The research data are low learning result andhigh level learning result on chemical equilibrium material measured by usingtest instrument choice and essay test with content validation each 80,6% and91,7%. The measurement of the reliability of questions was obtained fromCronbach's Alpha formula with a value of 0.73 for multiple choice tests and0.914 for the essay test. Data analysis using ANOVA Two Ways test. Theresult of the research shows that: (1) Low learning result of under guidedclass students in using computer simulation is higher than guided inquiryclass without computer simulation; (2) Higher student learning result inguided inquiry class using computer simulation higher than guided inquiryclass without computer simulation. So it can be concluded that guided inquirylearning using computer learning can student improve learning outcomes inchemical equilibrium material.